Bullying, mental health and friendship in Australian primary school children. Issue 4 (31st January 2018) - Bayer, Jordana K.; Mundy, Lisa; Stokes, Isobel; Hearps, Stephen; Allen, Nicholas; Patton, George
Abstract : Background: Frequent bullying predicts adolescent mental health problems, particularly depression. This population‐based study with young Australian primary school children aimed to determine the frequency and mental health correlates of bullying, and whether friendship could be protective. Method: Participants were a population‐based sample of 1221 children aged 8–9 years attending 43 primary schools in metropolitan Melbourne, Australia. Children were taking part in the Childhood to Adolescence Transition Study. Children completed online questionnaires at school to measure peer relations and emotional well‐being. Parents reported on their child's mental health in questionnaires sent to the home. Results: One in three children (29.2%) reported experiencing frequent bullying, defined as at least once a week. This included physical bullying alone (13.8%), verbal bullying alone (22.7%) and the combination (7.4%). Children who reported being frequently bullied self‐reported higher internalising symptoms compared with children who did not report frequent bullying ( M ( SD ) 1.6 (0.9) vs. 1.1 (0.8), p < .001). This difference was confirmed by parents' reports of their child's internalising symptoms ( M ( SD ) 2.4 (2.3) vs. 2.1 (2.0), p = .026, respectively). Amongst children who reported frequent bullying, those with a group of friends had better emotional well‐being. Conclusions: A substantial proportion of children report experiencing bullying on a weekly basis early in primary school. Given the prevalence of bullying in primary school and its relationship to children's mental health, we recommend effective school‐wide antibullying programmes. Further research can explore whether intervention to foster a group of friends around bullied children can improve their emotional well‐being.